Evasão escolar no ensino médio: um estudo sobre trajetórias escolares acidentadas - Marun, Dulcinéa Janúncio (2008)
This study aimed to examine the educational bumpy path of students who study the regular high school in the period night on the network of state public education, these trajectories characterized by abandonment and return, to the extent that these young people, for little or long time, once or several times, left the school and then returned to regular classes. The basics procedures for the collection of data were interviews, conducted in 2007, with four students (two male and two female), who were in that situation, in a school located in the city of Osasco, by means of which were collected information about the family life, school and work, and the main social relationships they fought. How procedure enhancement, were interviewed two teachers and educational coordinator responsible for the nocturnal period, to collect information both about their views on these students, and there were actions that seek some kind of strategy for the resolution of this problem. Data analysis was performed based on the contributions of Bourdieu (1982, 1989, 1998), especially as it pertains to these differentiations students in terms of cultural capital of origin, the influence of social relationships built, as well as the actual trajectory pregressa school. The main findings of this research can be summarized thus: both the expectations of the social fate of students who had dropped out and returns to school seem much more marked by the social position of origin than by the level of education achieved, the students incorporated the prospect of that the difficulties encountered in school say much respect themselves than the processes of education, but the educators find these problems, both individually as collectively do not create any initiative for a possible referral